2010
DOI: 10.1111/j.1471-4159.2010.07084.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes promote TNF-mediated toxicity to oligodendrocyte precursors

Abstract: Neuroinflammation and increased production of tumor necrosis factor (TNF) in the CNS have been implicated in many neurological diseases including white matter disorders periventricular leukomalacia and multiple sclerosis. However, the exact role of TNF in these diseases and how it mediates oligodendrocyte injury remain unclear. Previously, we demonstrated that lipopolysaccharide (LPS) selectively kills oligodendrocyte precursors (preOLs) in a non-cell autonomous fashion through the induction of TNF in mixed gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 64 publications
(77 reference statements)
6
68
0
Order By: Relevance
“…Indeed, TNF-a was demonstrated to cause degeneration of oligodendrocytes in the MS brain (4,24). Previous reports suggested that TNF-a inhibits survival and differentiation of OPCs in a model of spinal cord injury (SCI) (25), enhances oxidative stress-induced oligodendrocyte apoptosis (26), and mediates oligodendrocyte cell death through a TNFR1-dependent mechanism (27). Although our data support the previous work implicating TNF-a as a key cytokine that can dramatically influence oligodendrocyte biology (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, TNF-a was demonstrated to cause degeneration of oligodendrocytes in the MS brain (4,24). Previous reports suggested that TNF-a inhibits survival and differentiation of OPCs in a model of spinal cord injury (SCI) (25), enhances oxidative stress-induced oligodendrocyte apoptosis (26), and mediates oligodendrocyte cell death through a TNFR1-dependent mechanism (27). Although our data support the previous work implicating TNF-a as a key cytokine that can dramatically influence oligodendrocyte biology (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Oxidative stress and pro-inflammatory cytokines are found to contribute to demyelination and axonal damage in cultured cerebellar cells and promote oligodendrocyte progenitor cell death in microglia treated with LPS (46,47). It is also reported that microglia and astrocytes produce and secrete TNF␣, inhibiting the survival and differentiation of oligodendrocyte precursor cells (48,49). Consistent with these reports, a marked increase in Tnf␣ mRNA level was detected in GBDK brains, suggesting a proinflammatory environment.…”
Section: Bdksupporting
confidence: 62%
“…Mixed glial cultures and oligodendrocyte precursor cells (OPCs) were isolated with the differential attachment method as described previously (Chen et al, 2007; Kim et al, 2011; Li et al, 2008). In brief, the brains of P1–2 rat or mouse pups were isolated and placed in ice cold HBSS, followed by meninges removal under a dissection microscope.…”
Section: Methodsmentioning
confidence: 99%